2020
DOI: 10.1051/e3sconf/202017705007
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface waste management in the conditions of circular economy

Abstract: The article is devoted to the consideration of modern approaches to the subsurface waste management and the integrated development of the mineral resources base, the development of which requires consideration of the environmental, industrial, technological and economic aspects of this issue. The authors of the article note that it is advisable to use such modern management technologies as circular business models, 3R and 5R concepts, as well as logistics methods of waste management for the waste manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In the same area, courses for drivers and mechanics for salt cleaners were organized among young people (Chechens); some of the Chechens were promoted to responsible work as foremen for their exemplary work, head. plots and etc [11].…”
Section: Resultsmentioning
confidence: 99%
“…In the same area, courses for drivers and mechanics for salt cleaners were organized among young people (Chechens); some of the Chechens were promoted to responsible work as foremen for their exemplary work, head. plots and etc [11].…”
Section: Resultsmentioning
confidence: 99%
“…Although there have been various studies on industrial symbiosis and business models, no study includes a summary of tools and methods used to implement industrial symbiosis. The studies had the greatest emphasis on analyzing material flow from different perspectives, such as through measuring their circularity [44], looking for industrial waste that might be useful for other companies [24], evaluating supply chains [49], assessing the optimal combination of waste from a cost-recovery point of view [31], and developing tools to manage material flow in specific industries [45][46][47]. The studies include the development of business models that serve as templates to implement strategies that companies can adopt to create industrial symbiosis [7,20,21,51,53].…”
Section: Discussionmentioning
confidence: 99%
“…Angelis-Dimakis et al [24], using a technological platform, identified possibilities for industrial symbiosis between companies and/or regions, recommending innovative business models and evaluating financial viability and technical feasibility. Mochalova and Sokolova [45] focused on the use of waste from the mining industry. Kim et al [30] developed a methodology to evaluate alternatives to material flow exchange and steam in industrial parks, Santos and Magrini [46] performed this in a refinery, and Aid et al [22] identified the potential of a certain region.…”
Section: Objects Of Studymentioning
confidence: 99%